Iroquois - Bodden, Valerie (Mankato, Minnesota : Creative Education/Creative Paperbacks, 2018)
An introduction to the Iroquois lifestyle and history, including their forced relocation and how they keep traditions alive today. An Iroquois story recounts how the world began.
Includes bibliographical references (page 24) and index.
Keywords: Iroquois Indians -- Juvenile literature; Indians -- Juvenile literature; Iroquois Indians -- Juvenile literature; Indians; Iroquois Indians; Juvenile works; Instructional and educational works; Juvenile works; Instructional and educational works